KREDIT BERMASALAH DI PERBANKAN SYARI'AH DALAM PERSPEKTIF TEORI CACAT KEHENDAK - Gazali, Ahmad (Alhadharah: Jurnal Ilmu Dakwah, 2018)
The development of Islamic banking, especially in Indonesia, is currently very perspective. Therefore there is trust from the community must always be maintained. Efforts to develop and trust must support two aspects, namely the implementation of transparency with Islamic ethics and a sense of foundation that provides certainty and a sense of justice. As a sharia banking, the operational basis is Islamic law, thus the readiness of Islamic law must always exist and be able to overcome the development of the development of the Islamic banking world. This paper is only a small part of the discussion to be approved and legal norms of sharia banking are made.